Intestinal microbiota in obese children with non-alcoholic fatty liver disease depending on the gallbladder function - Stepanov, Yu. M.; Zavhorodnia, N. Yu.; Tatarchuk, O. M.; Klenina, I. A.; Hrabovska, O. I.; Zyhalo, E. V.; Petishko, O. P.; Vishnarevska, N. S.; Dolhopolova, V. V. (Zaporozhye Medical Journal, 2022)
Aim. To determine the features of the intestinal microbiota in obese children with non-alcoholic fatty liver disease (NAFLD) depending on the functional state of the gallbladder. Materials and methods. A total of 73 children aged 10–17 years (mean age – 12.15 ± 2.51 years) were examined. According to body mass index, transient elastography (Fibroscan®), and ultrasound data, the patients were divided into 3 groups: group I – 35 obese children with NAFLD and gallbladder hypokinesia, group II – 30 obese children with NAFLD and gallbladder normokinesia, group III (control) – 8 healthy children with normal weight and gallbladder normokinesia. Contractile function of the gallbladder was assessed by ultrasound examination after physiological food loading. Small intestinal bacterial overgrowth (SIBO) and lactose absorption were assessed with the hydrogen breath test (HBT) with lactose loading using a Gastrolyzer (Bedfont Scientific Ltd, UK). Qualitative and quantitative intestinal microbiome composition were studied using bacterial culture method with ten-fold dilutions (10-1–10-9) on standard sets of selective and differential-diagnostic culture media for the isolation of aerobic and anaerobic microbes. Fecal short-chain fatty acid (SCFA) content was evaluated with gas chromatography (Chromatec-Crystal-5000). Results. Lactose-dependent SIBO was observed in almost half of NAFLD patients (42.9 %) without significant differences depending on functional activity of the gallbladder. Patients with decompensated dysbiosis predominated in group I children (37.1 % of patients). In group II children, the subcompensated dysbiosis was more common (36.7 % of patients). The concentration of Lactobacillus and Enterococcus in group I patients was significantly 1.9 times (P < 0.05) and 1.4 times (P < 0.05) lower, respectively, than that in group IІ patients. The level of fecal acetic acid and butyric acid in group I children was 6.9 and 2.0 times (P < 0.05) increased, respectively, compared to control group, assuming bile acids involvement in the regulation of microbiome composition. Conclusions. Impaired contractile function of the gallbladder in NAFLD children is associated with a sharp decrease in the number of major symbionts of the intestinal microbiota as well as increased production of acetic and butyric SCFA.